Comparison of Fibrin and PLGA/fibrin Scaffolds for Chondrogenesis of Human Adipose Derived Stem Cells by Icariin - Batool Hashemibeni; Mohammad Mardani; Maryam Bahrami; Ali Valiani; Mohsen Setayesh Mehr; Majid Pourentezari (Journal of Kerman University of Medical Sciences, 2020)
Background: Recently, cartilage tissue engineering is the best candidate for regeneration of cartilage defects. We evaluated the potential of fibrin and PLGA/fibrin scaffolds in providing a suitable environment for growth and chondrogenic differentiation of human adipose derived stem cells (hADSCs) in the presence of icariin. Method: The Three-dimensional (3-D) PLGA scaffold was prepared using the solvent casting/salt leaching technique and the hybrid scaffold was fabricated by fibrin. hADSCs were isolated from human adipose tissue. 3-D PLGA/fibrin scaffolds were seeded with cultured hADSCs and analyzed 14 days later, Monolayer culture was used for the control group. The viabilities of cells in different groups were assessed by MTT. The expression of chondrogenic related genes, hypertrophic marker and Fibrotic marker were quantified by RT-PCR. Results:MTT results show that viability in the control group was significantly higher than those in the Fibrin and PLGA/Fibrin groups. Also viability in the PLGA/Fibrin group affected by icariin was higher than that in Fibrin group. The results of the real-time PCR showed that SOX9, Agg, Coll 2, and Coll 1 gene expression in the fibrin and PLGA/fibrin groups were significantly higher than those in the control group. Coll 10 gene expression in the fibrin group was higher in comparison to the control group but not significantly. type SOX9, Coll 2 and Coll 1 gene expression in the fibrin group was significantly lower compared to the PLGA/fibrin group. Conclusions: The study reveals that the corporation of PLGA with fibrin is an effective way to potentially enhance articular cartilage regeneration of hADSCs in the presence of icariin.